2013
DOI: 10.1002/cne.23410
|View full text |Cite
|
Sign up to set email alerts
|

Terminal distribution of the corticospinal projection from the hand/arm region of the primary motor cortex to the cervical enlargement in rhesus monkey

Abstract: To further our understanding of the corticospinal projection (CSP) from the hand/arm representation of the primary motor cortex (M1), high-resolution anterograde tracing methodology and stereology were used to investigate the terminal distribution of this connection at spinal levels C5 to T1. The highest number of labeled terminal boutons occurred contralaterally (98%) with few ipsilaterally (2%). Contralaterally, labeled boutons were located within laminae I – X, with the densest distribution found in lamina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
174
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(187 citation statements)
references
References 135 publications
(335 reference statements)
9
174
2
Order By: Relevance
“…This remarkable bilaterality of the CST projection is quantitatively distinct from observations in rats (Rouiller et al, 1991;Brus-Ramer et al, 2007). In contrast, the anatomy revealed in the present study is similar to the CST organization of the Old World monkey (Rosenzweig et al, 2009;Yoshino-Saito et al, 2010;Morecraft et al, 2013) and of humans (Nathan et al, 1990). Furthermore, in this study, we observed the spiking response of spinal neurons induced by repetitive CST stimulation on laminae VII-VIII of the spinal gray matter ipsilateral to the pyramidal stimulation with relatively short segmental latency (1.8 ms), which suggested oligosynaptic linkage from the CST.…”
Section: Bilateral Spinal Terminations Of the Corticospinal Tractcontrasting
confidence: 69%
See 1 more Smart Citation
“…This remarkable bilaterality of the CST projection is quantitatively distinct from observations in rats (Rouiller et al, 1991;Brus-Ramer et al, 2007). In contrast, the anatomy revealed in the present study is similar to the CST organization of the Old World monkey (Rosenzweig et al, 2009;Yoshino-Saito et al, 2010;Morecraft et al, 2013) and of humans (Nathan et al, 1990). Furthermore, in this study, we observed the spiking response of spinal neurons induced by repetitive CST stimulation on laminae VII-VIII of the spinal gray matter ipsilateral to the pyramidal stimulation with relatively short segmental latency (1.8 ms), which suggested oligosynaptic linkage from the CST.…”
Section: Bilateral Spinal Terminations Of the Corticospinal Tractcontrasting
confidence: 69%
“…For the latter purpose, excitatory and/or inhibitory synaptic responses evoked by electrical stimulation at the pyramid were recorded from spinal gray matter (field potentials) and motoneurons (intracellular recordings) at the lower cervical level. Bilateral projections from one hemisphere have been reported in other primate species (Rosenzweig et al, 2009;Yoshino-Saito et al, 2010;Morecraft et al, 2013), in which they might provide neural substrate for some recovery after spinal cord injury (Rosenzweig et al, 2010). Therefore, we also characterized the distribution of CST axons and synaptic responses of CST stimulation at different laminae on both sides of the spinal cord.…”
Section: Q3mentioning
confidence: 96%
“…2) [3, 14, 3941]. Interestingly, evidence for the crossing of ipsilateral fibers at spinal levels was also observed in multiple studies [3, 39, 40]; therefore, the presence of ipsilateral fibers suggested by BDA only indicates that these fibers descend ipsilaterally and there is a high likelihood that these fibers will re-cross and end up innervating contralateral neurons.…”
Section: Icst In Non-human Primatesmentioning
confidence: 88%
“…When the termination patterns of these ipsilateral fibers were assessed, they were found to cover spinal laminae V–IX, with the highest density (~80%) of innervation in ipsilateral lamina VIII, and very sparse termination in ipsilateral lamina IX (Table 2, Fig. 2) [3, 14, 3941]. The consistent finding that the majority of iCST fibers terminate at lamina VIII challenges the functional significance of iCST fibers since lamina VIII mainly harbors commissural interneurons that project through the midline to the contralateral cord, thus largely contributing to contralateral movement control [46].…”
Section: Icst In Non-human Primatesmentioning
confidence: 99%
“…In selected cases, electrophysiological microstimulation was used in combination with ketamine (10 mg/kg) and diazepam (1.0 mg/kg) to map M1, LPMC and M2 which has been described in detail in our previous reports (McNeal et al, 2010; Morecraft et al, 2007a, 2013a). Briefly, stimulation was performed using a Grass Square Pulse Stimulator system (model S28; Grass Technologies, West Warwick, RI) with an attached tungsten electrode (impedance 0.5–1.5 MΩ).…”
Section: Methodsmentioning
confidence: 99%